2018
DOI: 10.1002/jcb.28042
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of autophagy inducer, simvastatin on alcohol‐induced liver disease in a rat model

Abstract: Alcoholic liver disease (ALD) encompasses a variety of liver injuries with various underlying mechanisms but still no effective treatment. So we aimed to monitor the influence of simvastatin on alcohol‐induced liver injury and elucidate the underlying mechanisms of its cytoprotective effect. Thirty male albino rats were randomly divided into five equal groups. Group 1 (control): received a standard diet; group 2: received simvastatin (10 mg kg−1 day −1) once a day orally for 8 weeks; group 3: received 20% etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
1
7
0
1
Order By: Relevance
“…Consistent with earlier findings that autophagy can protect animals from alcohol-induced liver injury and steatosis, several recent studies confirmed the ameliorative effects of hepatic autophagy in multiple ALD animal models, including an 8-week alcohol-fed rat model [97] and an alcohol-plus-LPS ALD mouse model [98]. Augmenter of liver regeneration (ALR) is a factor that can promote liver growth and it has been shown to protect against acute liver injury from variable insults [99].…”
Section: Roles Of Autophagy During Pathogenesis Of Aldsupporting
confidence: 85%
“…Consistent with earlier findings that autophagy can protect animals from alcohol-induced liver injury and steatosis, several recent studies confirmed the ameliorative effects of hepatic autophagy in multiple ALD animal models, including an 8-week alcohol-fed rat model [97] and an alcohol-plus-LPS ALD mouse model [98]. Augmenter of liver regeneration (ALR) is a factor that can promote liver growth and it has been shown to protect against acute liver injury from variable insults [99].…”
Section: Roles Of Autophagy During Pathogenesis Of Aldsupporting
confidence: 85%
“…Meanwhile, upon simvastatin treatment, the treated group showed a statistically significant decrease of liver enzymes indicating its ameliorative effect. The results revealed low ALT and AST levels in the ethanol-treated group with the lowest levels observed in ethanol group that was co-treated with simvastatin [12].…”
Section: Liver Enzymes Resultsmentioning
confidence: 90%
“…Gu reported that simvastatin alleviated airway inflammation and remodeling by upregulating autophagy in mouse models of asthma . Atef found that simvastatin, an autophagy inducer, was able to prevent and reverse alcohol‐induced liver changes partly by the induction of autophagy, attenuation of oxidative stress, inflammation, and endoplasmic reticulum stress‐induced apoptosis . Therefore, moderate enhancement of autophagy may be the reason why simvastatin may alleviate corpus cavernosum fibrosis and thus improve erectile function.…”
Section: Discussionmentioning
confidence: 99%